Implementasi Pembelajaran Catur Guru Dalam Membentuk Karakter Siswa - Ida Ayu Dwi Lestari; Ni Komang Sutriyanti (Jurnal Penelitian Agama Hindu, 2020)
This study aims to describe the implementation of Chess Teacher learning in shaping the character of students in Sekolah Dasar Negeri 2 Kaba-Kaba, where it is applied by school teachers in class learning, with Catur Guru material, namely Guru Swadyaya, Guru Rupaka, Guru Pengajian, Guru Wisesa. The formation of character through schools is a noble effort that is urgent to do. In fact, when talking about the future, schools are responsible not only for producing students who excel in science and technology, but also in identity, character and personality. In character building, the family environment and the school environment have a very important role, because the family as the first and foremost educator functions to carry religious, cultural, ethical, moral, and spiritual values to their children. While the school as a formal educational institution is tasked to transform knowledge and socio-cultural values that can produce quality human resources and have high competitiveness. Thus it can be said that the formed behavior that is characterized is strongly influenced by the family environment and the school environment as well as the wider school environment (community), in addition to the potential and beliefs or the attitude of confidence possessed by individuals.